Activity profile and between-match variation in elite male field hockey - Sunderland, C. D.; Edwards, P. L. (The Journal of Strength and Conditioning Research, 2017)
This study aimed to (a) provide a position-specific activity profile for elite male hockey players, (b) determine if the activity profile was altered by the introduction of the "self-pass" rule, and (c) provide information relating to match-to-match variability in elite male field hockey. The activity of 28 elite male field hockey players was analyzed over 2 seasons totaling 395 player-match analyses using Global Positioning Satellite technology. Total distance, high-speed running (>15.5 km/h), sprinting (>20 km/h), and mean speed were recorded. Players were categorized into 4 positions: fullback (FB), halfback (HB), midfield (M), and forward (F). Data were analyzed using a 2-way analysis of variance (season, position) and between-match coefficients of variation (CV). The time played differs with position (FB: 65.5 ± 5.3, HB: 49.5 ± 11.5, M: 45.9 ± 7.1, F: 39.5 ± 5.4 minutes; p < 0.0005) and thus affected the activity profile. Total distance covered was greater for fullbacks (FB: 8,001 ± 447, HB: 6,435 ± 1,399, M: 6,415 ± 908, F: 5,844 ± 762 m, p < 0.001), and mean speed and percentage time spent high-speed running and sprinting were greater for forwards than all other positions (HSR: FB: 6.8 ± 1.0, HB: 8.8 ± 1.3, M: 10.7 ± 1.2, F: 13.5 ± 1.8%, p < 0.001). The activity profile did not differ with the introduction of the self-pass. Match-to-match variability (CV) ranged from 5.0% to 22.0% for total and sprint distance, respectively. This is the first study to present an activity profile of elite men's field hockey and its associated variability and demonstrates that each position is unique, and therefore, training and recovery should be position specific.